Knowledge in the Historical Perspective of Coming-To-Be and Passing-Away - Yildirim, Erdogan (2018)
Since the last decades of the 20th century the meaning and content of knowledge has dramatically changed. This necessitates adopting a historical perspective in approaching the questions of knowledge. But so far all the efforts of putting knowledge in a historical perspective since Hegel's historization of Spirit either suffer from the limitations of the presupposition of the One (Spirit or Being) or fail to ground the historicity of knowledge on the history of coming-to-be and passing-away. Moving from Heidegger's history of Being' toward the Aristotelian understanding of coming-to-be and passing away as a process of becoming has the potential to open up new avenues in approaching the historical question of knowledge as well as establishing its relation with the never complete ground (hypokeimenon) of the entities (ousia) as its historical a priori condition(s) of possibility.
Keywords: Aristotle; Heidegger; Becoming; coming-to-be and passing-away; Faith; historical a priori; Knowledge; poiein and paschein; replacement of God; Spirit